Medical Ethics and New Public Management in Sweden - Hansson, Sven Ove (Cambridge quarterly of healthcare ethics, 2014)
In order to shorten queues to healthcare, the Swedish government has introduced a yearly “queue billion” that is paid out to the county councils in proportion to how successful they are in reducing queues. However, only the queues for first visits are covered. Evidence has accumulated that queues for return visits have become longer. This affects the chronically and severely ill. Swedish physicians, and the Swedish Medical Association, have strongly criticized the queue billion and have claimed that it conflicts with medical ethics. Instead they demand that their professional judgments on priority setting and medical urgency be respected. This discussion provides an interesting illustration of some of the limitations of new public management and also more generally of the complicated relationships between medical ethics and public policy.